Asymptomatic Hepadnaviral Persistence and Its Consequences in the Woodchuck Model of Occult Hepatitis B Virus Infection - Mulrooney-Cousins, Patricia M. (J Clin Transl Hepatol, 2015)
Woodchuck hepatitis virus (WHV) is molecularly and pathogenically closely related to hepatitis B virus (HBV). Both viruses display tropism towards hepatocytes and cells of the immune system and cause similar liver pathology, where acute hepatitis can progress to chronic hepatitis and to hepatocellular carcinoma (HCC). Two forms of occult hepadnaviral persistence were identified in the woodchuck-WHV model: secondary occult infection (SOI) and primary occult infection (POI). SOI occurs after resolution of a serologically apparent infection with hepatitis or after subclinical serologically evident virus exposure. POI is caused by small amounts of virus and progresses without serological infection markers, but the virus genome and its replication are detectable in the immune system and with time in the liver. SOI can be accompanied by minimal hepatitis, while the hallmark of POI is normal liver morphology. Nonetheless, HCC develops in about 20% of animals with SOI or POI within 3 to 5 years. The virus persists throughout the lifespan in both SOI and POI at serum levels rarely greater than 100 copies/mL, causes hepatitis and HCC when concentrated and administered to virus-naïve woodchucks. SOI is accompanied by virus-specific T and B cell immune responses, while only virus-specific T cells are detected in POI. SOI coincides with protection against reinfection, while POI does not and hepatitis develops after challenge with liver pathogenic doses >1000 virions. Both SOI and POI are associated with virus DNA integration into the liver and the immune system genomes. Overall, SOI and POI are two distinct forms of silent hepadnaviral persistence that share common characteristics. Here, we review findings from the woodchuck model and discuss the relevant observations made in human occult HBV infection (OBI).